2012
DOI: 10.1021/ar300086n
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Exploiting Polar−π Interactions with Fluorinated Aromatic Amino Acids

Abstract: Fluorination has become an increasingly attractive strategy in protein engineering for both basic research and biomedical applications. Thus researchers would like to understand the consequences of fluorination to the structure, stability, and function of target proteins. Although a substantial amount of work has focused on understanding the properties of fluorinated aliphatic amino acids, much less is known about fluorinated aromatic residues. In addition, polar-π interactions, often referred to as aromatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 61 publications
0
96
0
1
Order By: Relevance
“…Therefore, the peptide AzoChig1 (GYDP-AMPP-GTWG) was designed, in which the two central amino acids Glu5 and Thr6 of chignolin's four-residue turn sequence were substituted by AMPP (Fig. 20,21 However, systematic studies towards structure-guiding effects of fluorinated amino acids have mostly focused on a-helical systems 19,22 and only a limited number of approaches for fluorination of specific b-sheet positions have been reported, so far. Besides, peptidomimetic AzoChig2 (GYDP-AMPP-GT(5FW)G) with a 5-fluoro-Ltryptophan (5FTrp, 5FW) residue instead of Trp9 was synthesized to enhance key hydrophobic interactions between aromatic Tyr2 and Trp9.…”
mentioning
confidence: 99%
“…Therefore, the peptide AzoChig1 (GYDP-AMPP-GTWG) was designed, in which the two central amino acids Glu5 and Thr6 of chignolin's four-residue turn sequence were substituted by AMPP (Fig. 20,21 However, systematic studies towards structure-guiding effects of fluorinated amino acids have mostly focused on a-helical systems 19,22 and only a limited number of approaches for fluorination of specific b-sheet positions have been reported, so far. Besides, peptidomimetic AzoChig2 (GYDP-AMPP-GT(5FW)G) with a 5-fluoro-Ltryptophan (5FTrp, 5FW) residue instead of Trp9 was synthesized to enhance key hydrophobic interactions between aromatic Tyr2 and Trp9.…”
mentioning
confidence: 99%
“…The moderate stability even makes HP36 a good model protein used in the coating layer of nanoparticles for a laser‐induced thermal study . In previous studies, various forces and factors, including hydrogen bonding, aromatic–aromatic interactions, aromatic–proline interactions, hydrophobic interactions, cation–π interactions and steric effects, have been shown to affect the structure of HP36 . Recently, our study has also demonstrated that the proline puckering effect from various 4‐substituted proline derivatives can weaken the Pro…Trp interaction and induce hydrophobic effects as well, thereby affecting the stability of HP36 .…”
Section: Introductionmentioning
confidence: 68%
“…Section 3.2 in Synthesis file) and typically in crystals of molecules with aryl and perfluoroaryl sub-units. [40][41][42][43][44] The on-surface 2D network is mainly comprised of regular pores enclosed by six Zn(II) porphyrin molecules 1 (Fig. 2, Fig.…”
Section: Resultsmentioning
confidence: 99%